Molecular and pharmacological characterization of insulin icodec: a new basal insulin analog designed for once-weekly dosing. Issue 1 (19th August 2021) - Nishimura, Erica; Pridal, Lone; Glendorf, Tine; Hansen, Bo Falk; Hubálek, František; Kjeldsen, Thomas; Kristensen, Niels Rode; Lützen, Anne; Lyby, Karsten; Madsen, Peter; Pedersen, Thomas Åskov; Ribel-Madsen, Rasmus; et al.
Abstract : Introduction: Insulin icodec is a novel, long-acting insulin analog designed to cover basal insulin requirements with once-weekly subcutaneous administration. Here we describe the molecular engineering and the biological and pharmacological properties of insulin icodec. Research design and methods: A number of in vitro assays measuring receptor binding, intracellular signaling as well as cellular metabolic and mitogenic responses were used to characterize the biological properties of insulin icodec. To evaluate the pharmacological properties of insulin icodec in individuals with type 2 diabetes, a randomized, double-blind, double-dummy, active-controlled, multiple-dose, dose escalation trial was conducted. Results: The long half-life of insulin icodec was achieved by introducing modifications to the insulin molecule aiming to obtain a safe, albumin-bound circulating depot of insulin icodec, providing protracted insulin action and clearance. Addition of a C20 fatty diacid-containing side chain imparts strong, reversible albumin binding, while three amino acid substitutions (A14E, B16H and B25H) provide molecular stability and contribute to attenuating insulin receptor (IR) binding and clearance, further prolonging the half-life. In vitro cell-based studies showed that insulin icodec activates the same dose-dependent IR-mediated signaling and metabolic responses as native human insulin (HI). The affinity of insulin icodec for the insulin-like growth factor-1 receptor was proportionately lower than its binding to the IR, and the in vitro mitogenic effect of insulin icodec in various human cells was low relative to HI. The clinical pharmacology trial in people with type 2 diabetes showed that insulin icodec was well tolerated and has pharmacokinetic/pharmacodynamic properties that are suited for once-weekly dosing, with a mean half-life of 196 hours and close to even distribution of glucose-lowering effect over the entire dosing interval of 1 week. Conclusions: The molecular modifications introduced into insulin icodec provide a novel basal insulin with biological and pharmacokinetic/pharmacodynamic properties suitable for once-weekly dosing. Trial registration number: NCT02964104 .